Radiological predictors of PCP in HIV-positive adults in South Africa: a matched case-control study - Wills, Nicola (Department of Medicine, 2024)
Background Definition of chest X-ray (CXR) features associated with laboratory-confirmed pneumocystis pneumonia (PCP) among HIV-positive adults is needed to improve diagnosis in high-burden settings. Methods We conducted a case-control study involving HIV-positive adults with laboratory-confirmed PCP and a matched cohort with non-PCP respiratory presentations at regional hospitals in Cape Town, South Africa (2012 - 2020). The primary objective was to identify CXR features associated with confirmed PCP diagnosis and severe PCP (defined by hypoxia, ICU referral/admission, and/or in-hospital death). We explored the performance of logistic regression models, incorporating selected clinical and CXR predictors, for PCP diagnosis and severe PCP. Results Records from 104 adults (52 PCP cases and 52 non-PCP controls) were included. Diffuse versus patchy ground glass opacification was associated with increased odds of PCP diagnosis (adjusted odd's ratio (aOR) 6.2, 95% confidence interval (CI) 1.6 - 28.9, p = 0.01) and severe PCP (aOR 4.5, 95%CI 1.6 - 14.4, p = 0.008). Consolidation was associated with severe PCP (aOR 3.3, 95%CI 1.2 - 11.0, p =0.03) as was increasing ground glass zone involvement (aOR 2.1 for each one-unit increase in involved zone; 95% CI, 1.4 - 3.2, p = 0.0004). Models incorporating hypoxia (hypoxia model) or tachypnoea (respiratory rate model) with diffuse ground glass opacities, absence of pleural effusion or reticular/reticulonodular changes on CXR performed well in predicting PCP (area under the receiver operating characteristic curve 0.828 (hypoxia model) and 0.857 (respiratory rate model)). Conclusions CXR evaluation alongside bedside clinical information offers good accuracy for discriminating definite PCP from other HIV-associated respiratory diseases